Analysis of the Mixed Code of West Java Governor Dedi Mulyadi: A Case Study of Viral Content "Naughty Boys Are Sent To Military Barracks" - Priadi, Ribut; Eriska, Peny (Persepsi: Communication Journal, 2025)
This study aims to analyze the form and meaning of the use of mixed codes in the viral video content of the Governor of West Java, Dedi Mulyadi, entitled "Naughty Children Brought to Military Barracks". The approach used is qualitative descriptive with literature study techniques, see and note techniques on videos uploaded on @dedimulyadiofficial TikTok account. The results of the study show that the code mix used is a mixture of inward codes, in the form of a combination of formal Indonesian and informal spoken language. This mixed-code strategy is not only linguistic, but also reflects a political communication strategy that is populist, paternalistic, and responsive to digital audiences. Dedi Mulyadi positions himself as an authority figure who is close to the people, especially families and children, by using simple, persuasive, and emotional language. Mix code serves as a tool to build a symbolic relationship between leaders and society and form an image of a leader who is friendly, active, and down-to-earth. These findings show that in a digital space like TikTok, language becomes an important instrument in the construction of political image and effective public communication.